Factors contributing to the development of cerebral malaria. II. Endotoxin. - Usawattanakul, W; Tharavanij, S; Warrell, D; Looareesuwan, S; White, N; Supavej, S; Soikratoke, S (1985)
Limulus amoebocyte lysate test (LALT) was used to detect endotoxin-like substances in the plasma of 15 patients with cerebral malaria, 28 patients with uncomplicated falciparum malaria and 30 healthy controls. On admission, 67% of cerebral malaria patients were positive, whereas only 21.4% of uncomplicated malaria patients and none of controls were positive. Among uncomplicated malaria cases, four of eight patients with parasitaemia over 90,000/mm3 were LALT positive whereas only two of 20 patients with parasitaemia of less than 90,000/mm3 were positive. A follow-up study in cerebral malaria patients showed some variation in LALT positivity rate from day to day (85.7% on day 1, 53.3% on day 3 and all negative on discharge from hospital). LALT positivity bore no relationship to gram negative bacteraemia. Leucocytosis and elevated serum enzymes were more frequently found in LALT-positive patients. Our results suggest that endotoxin (LALT positivity) of the plasma of malaria patients is derived from either the parasites themselves or from the gut. It relates to parasitaemia, leucocytosis and elevated serum enzymes, but not to the clinical syndrome of cerebral malaria.